Keeping the spark alive: preventing burnout at work while increasing work engagement. (2nd September 2020) - Bilginoğlu, Elif; Yozgat, Uğur
Leaders who ignite spirit, encourage passion and light the spark in employees to create the fire in their work environment are called the 'sparking leaders'. This study investigates mainly the impact of sparking leaders on the employees' work engagement, burnout and intention to leave the organisation and on the other side the impact of self-efficacy on the burnout and intention to leave the organisation, additionally. This study was conducted in Istanbul on participants working mainly in healthcare sector. Data of 291 respondents were subjected to exploratory factor analysis, reliability and convergent/discriminant validity analyses, and path analysis using SPSS and LISREL. Findings revealed that sparking leadership, as evaluated by employees, predicted work engagement and decreased their burn out as well as their intention to leave the organisation. The findings also revealed that the self-efficacy of the employees played an important role on decreasing their burn-out and intention to leave the organisation.